MODEL LIFE BASED LEARNING PADA LEMBAGA PENDIDIKAN DASAR ISLAM DI KEDIRI: TINJAUAN PENERAPAN PENDIDIKAN ISLAM TRANSFORMATIF - Marita Lailia Rahman; Diana Nur Sholihah; Farah Diba (EBTIDA': Jurnal Pendidikan Dasar Islam, 2025)
Abstract Transformative education emphasizes that the success of learning lies in the opportunity for learners to assess their own learning experiences. Therefore, measuring the quality of education needs to prioritize a more humanistic approach. One form of empowerment is designing a learning model that honors the learners. Life Based Learning is a series of learning activities connected to real-life experiences and provides space for the development of individual skills. This learning is understood as a process of learning from all aspects of life, at any time and from any source. This study aims to describe teachers' perceptions of Life Based Learning, its implementation, and its evaluation process. The study uses a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. Data analysis involves collection, presentation, reduction, and drawing conclusions. The study results show that teachers view Life Based Learning as a model that encourages students to acquire knowledge and skills to understand the essence of life, solve problems, and live harmoniously. The implementation of Life Based Learning at MIN 2 Kediri is integrated into teaching and learning activities under both the 2013 Curriculum and the Merdeka Curriculum, including habits before, during, and after learning, as well as activities at home and in the community through six dimensions. Evaluation uses assessments of both the process and outcomes. These findings confirm that Life Based Learning is relevant for enhancing the quality of education in a sustainable and comprehensive manner. Keywords: Life-Based Learning Model, Islamic Primary Education Institutions, Transformative Islamic Education. Abstrak Pendidikan transformatif menekankan bahwa keberhasilan pembelajaran terletak pada kesempatan bagi peserta didik untuk menilai pengalaman belajarnya sendiri. Pengukuran kualitas pendidikan karenanya perlu mengedepankan pendekatan yang lebih humanis. Salah satu bentuk pemberdayaan tersebut ialah merancang model pembelajaran yang memuliakan peserta didik. Life Based Learning merupakan rangkaian pembelajaran yang terhubung dengan realitas kehidupan dan memberi ruang bagi pengembangan kemampuan individu. Pembelajaran ini dipahami sebagai proses belajar dari seluruh aspek kehidupan, kapan pun dan dari sumber apa pun. Penelitian ini bertujuan mendeskripsikan persepsi guru tentang Life Based Learning, pelaksanaannya, serta proses evaluasinya. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Analisis data meliputi pengumpulan, penyajian, reduksi, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa guru memandang Life Based Learning sebagai model yang mendorong peserta didik memperoleh pengetahuan dan kecakapan untuk memahami hakikat hidup, memecahkan masalah, dan menjalani kehidupan secara harmonis. Pelaksanaan Life Based Learning di MIN 2 Kediri diintegrasikan ke dalam KBM pada kurikulum 2013 maupun Kurikulum Merdeka, termasuk pembiasaan sebelum, saat, dan setelah KBM, serta aktivitas di rumah dan lingkungan melalui enam dimensi. Evaluasinya menggunakan penilaian proses dan hasil. Temuan ini menegaskan bahwa Life Based Learning relevan diterapkan untuk meningkatkan kualitas pembelajaran secara berkelanjutan dan menyeluruh sekolah. Kata Kunci: Model Life Based Learning, Lembaga Pendidikan Dasar Islam, Pendidikan Islam Transformatif.